MULTITHERAPY PROTOCOL FOR THE TREATMENT OF ACNE SCARS - CASE REPORT - Silva Marcondes, Bruna; Feldmann, Cristina; Cesar Trindade, Alessandra (Health and Society, 2022)
Acne scars are one of the most common skin diseases and can affect people’s quality of life, so it has increased the search for treatments that can reduce or solve this imperfection. Several studies have been proposed with different onliest or combined therapies, including microneedling associated with PRP. The main objective of this study was to describe a clinical case of a treatment of post acne scars through the microneedle associated with PRP and iPRF activated with oZônio. The results showed improvement in texture and softening in post acne scars. It can be concluded that microneedle treatment associated with ozone-activated PRP and is safe and efficient in the treatment of post-acne scars.